A Retrospective Study on Peripartum cardiomyopathy, Recent Trends and disease profile, study at tertiary centre of Bihar - Aman Sinha; Satish K. (Student's Journal of Health Research Africa, 2024)
Background: Peripartum Cardiomyopathy (PPCM) is a rare but serious cardiovascular condition that affects women in the peripartum period. The aim of this study is to comprehensively investigate the recent trends and disease profile of PPCM among patients at a tertiary center in Bihar. Methods: A retrospective study was conducted which included 50 female participants who met specific inclusion criteria, such as being aged 18 years or older, having a confirmed PPCM diagnosis, and having complete medical records available for analysis. Data collection encompassed demographic information, clinical presentation, diagnostic criteria, echocardiographic findings, laboratory results, and treatment modalities employed. Statistical analysis involved descriptive statistics, categorical and continuous variable presentations, and the use of SPSS ver. 18 for data analysis. Results: The mean age at PPCM diagnosis was 32.5 years, with 60% being parous and 40% nulliparous. Clinical symptoms included dyspnea (84%), fatigue (76%), and edema (70%). Echocardiographic findings revealed compromised cardiac function, with a mean LVEF of 35%. Laboratory results demonstrated elevated BNP and troponin levels. Treatment approaches were diverse, including medications, interventions, and lifestyle modifications. Complications included arrhythmias (20%), thromboembolic events (10%), and cardiogenic shock (14%). The overall survival rate was 84%, with a mortality rate of 16%. Conclusion: The study provides valuable insights into the clinical profile, diagnosis, treatment, and outcomes of PPCM in a retrospective cohort. The findings highlight the complex nature of PPCM and the importance of early recognition and comprehensive management strategies in improving patient outcomes. Further research and awareness efforts are needed to enhance the understanding and management of this challenging condition. Recommendations: Medical practitioners should be educated about PPCM to aid early diagnosis. Obstetricians, cardiologists, and other professionals collaborate for multidisciplinary treatment. Frequent cardiac monitoring for high-risk pregnant and postpartum women. More research on risk factors and innovative PPCM treatments.